Development of a scenario-based approach for responding to change in fishery systems: a case study in the small-scale fisheries of South Africa's Southern Cape - Gammage, Louise Carin (Department of Environmental and Geographical Science, 2019)
Small-scale fishers and the communities they support face a range of challenges brought on by change in their marine social-ecological systems (SES). The resulting complexity and uncertainty hamper their ability to achieve sustainability while holding implications for decision-making at various scales: fishers need to respond proactively to change at smaller scales of operation while managers need to apply the principles of ecosystem-based management approaches such as an ecosystem approach to fisheries management (EAF) at larger scales. Using the small-scale fishing communities of South Africa’s southern Cape as a case study, this thesis explores how structured decision-making tools (specifically causal mapping, Bayesian belief networks and scenario planning) can be applied in an interactive and iterative scenario-based approach with disenfranchised fishers in support of decision-making at multiple scales. Specifically, this thesis aims to (1) determine and describe major stressors in the fishery system of the southern Cape using the perspectives from the crew component of its line fishery; (2) establish what interactions and feedback loops (drivers of change) exist and interact at various scales; (3) use Bayesian belief network modelling in an iterative participatory process to establish the prominent drivers of change within the fishery system (from the crew perspective); (4) develop, together with fishers, four stories of what the future may hold for one of the towns using an iterative participatory scenario planning exercise, based on some of the principles of transformative scenario planning approaches; (5) evaluate the contextual suitability of the application of the various tools used throughout the research process and recommend next steps in a larger scenario planning process; and (6) create an opportunity for fishers to engage in a process that could enhance their understanding of possible change response strategies through learning, thereby increasing adaptive capacity in the support of the implementation of an EAF in South Africa. As a start, drivers of change were established and documented, complementing earlier research. This was done to ensure that all user groups’ views were represented in an initial causal map showing the drivers of change in the fishery system. In the causal mapping process, stakeholders from towns across the research area mapped out drivers of change in an iterative process. The causal maps not only helped to frame the system but also revealed important hidden drivers of change as well as feedback loops. The Bayesian belief network and scenario story development took place in the town of Melkhoutfontein. Bayesian belief networks provided insights into system uncertainty while serving as a problem reframing tool. The outputs of both the causal maps and Bayesian networks were then used to construct four scenario stories depicting possible futures in 30 years, based on inputs obtained from research participants in a visioning workshop. These scenarios not only provided examples of plausible futures under certain conditions but also promoted new ways of thinking about the drivers of change and their likely effects, highlighting the interconnectedness in the system. Implementing the overarching approach has provided marginalised fishers with an opportunity to freely air their views while engaging with new tools. The process does not only benefit fishers and their communities (at the small scale) but also provide valuables insights into how fishers view and experience the marine SES of the southern Cape. Moreover, the approach has identified ways in which challenges presented by scale in SES can be better addressed to ensure more effective decision-making in the pursuit of sustainability. This understanding and insight are integral for moving closer to the implementation of the EAF in South Africa, where the integration of the social dimensions of marine social-ecological systems into coherent evaluation and planning continues to be problematic.